Characteristics and outcomes of the drug patent linkage system in China - Xue-Fang Yao (Globalization and Health, 2024)
Abstract Background On July 4, 2021, China officially introduced the drug patent linkage system, which has made more localized adjustments than have similar systems in the US and South Korea. This study describes the characteristics and outcomes of China’s patent linkage system. Methods For this study, we used the database of China’s patent information registration platform for marketed drugs to capture all listed patents and patent certifications from June 25, 2021, to June 30, 2023. We used descriptive statistics for the above data to assess the impact of patent linkage on branded drug manufacturers, generic drug manufacturers, and the public’s access to medicines. Results During the study period, the patents of 632 branded drugs were listed, and 5058 ANDAs submitted patent certifications to the Registration Platform. Of these 632 branded drugs, 462 (73.1%) drugs were approved before the year of patent registration, and the average number of listed patents per drug was 1.8, with a standard deviation of 1.4. However, of these 5058 ANDAs, P1 certifications accounted for 85.1%, and P3 and P4 certifications accounted for 16% combined. In addition, according to the detailed statistics of P2 certifications, we found that the proportion of patent invalidation cases was 46.4%. The remaining validity of the patents corresponding to P3 certifications was longer, with a median value of 17 months, and the IQR was 10-30.75, ranging from − 2 to 204 months. Conclusions China’s patent linkage aims to promote the balance of multiple interests —innovation, imitation and public health—and has its own system characteristics. Patent listing and patent certification are the key indicators reflecting the implementation effect of the system. From the perspective of system outcomes, ANDAs have been connected to the patent linkage system in an orderly manner, but the growth of patent challenges is not obvious. Moreover, manufacturers of foreign branded drugs that have not yet entered the Chinese market need to pay more attention to the role of patent listing.